THE MAINTENANCE OF THE DANCE OF BAMBU GILA: THE FUNCTION OF PAWANG AND MANTRA - helmina Kastanya (Widyariset, 2015)
The dance of bambu gila or barasuwen is unique because its mystical aspect. Its aspect is shown by the existence of mantra and sage as the important part and can not be separated from the performance of the dance of bambu gila. Today, this dance is rarely performed because some factors that are the death of sage of the dance, mantra closed inheritance, the shift of enthusiasm of young generation and the society. The aim of the study is to reveal the role of mantra and sage in the maintenance effort of bambu gila dance in the Province of Maluku. The method of this study is qualitative method, while the theory are semiotics, to interprete the mantra text, and literature sociology, to reveal how important the role of mantra and sage in the maintenance of the dance of bambu gila is. The result shows that the mantra and sage have the important role in the dance. The function of the dance are begging the assist from the ancestor, blessing, and acknowledging the supreme power of God. The function of mantra is to process the ancestor soul and the magical spirit in order to control the bamboo and its dancer. The key of maintenance of the dance is awareness of the sage in doing more open mantra inheritance and its ritual to the society.